The Meaning of Love Language in Student Relations: Edmund Husserl's Phenomenological Approach - Afdi Maulfianti; Pudja Lastari (MID Publisher International, 2023)
Romantic relationships among university students constitute a form of interpersonal communication that involves emotional expression, affection, and the construction of meaning through various communicative practices. One prominent form of affective communication in romantic relationships is the concept of love language introduced by Gary Chapman. This study aims to analyze the meaning of love language among student couples at Mathla’ul Anwar University Banten based on their subjective experiences and Islamic values. This research employed a qualitative approach based on Edmund Husserl’s transcendental phenomenology. The study applied a constructivist paradigm, while data were collected through in-depth interviews, observation, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings reveal that the dominant forms of love language among student couples include words of affirmation, quality time, and acts of service. Love language is interpreted as a form of attention, emotional appreciation, presence, and psychological support within romantic relationships. Furthermore, the values of mahabbah and rahmah serve as moral foundations in maintaining relationships while adhering to religious boundaries and social ethics. This study demonstrates that affective communication in students’ romantic relationships is not solely emotional in nature but is also shaped by spiritual and cultural values that influence the subjective meaning of love.